STEM-based ecology module development for differentiated learning in agroecosystem of junior high schools - Slamet Hariyadi; Jekti Prihatin; Nikmatin Mabsutsah (Research and Development in Education (RaDEn), 2024)
The study aims to describe the development of an integrated STEM-based ecological module to improve creative thinking skills and learning outcomes in agroecosystems in differentiated learning. The research method is developing the Thiagarajan Four-D model with a one-group pretest-posttest design. Validation data were obtained from module validation, learning design, creative thinking skills rubric, and learning outcome test. Practicality is determined based on teacher and student responses, learning implementation, and readability tests. Effectiveness is determined based on the N-gain value of creative thinking skills and learning outcomes. The results of the study were very significant: the score of module validation was 90.21, the result of all practice indicators was 92.9, the N-gain effectiveness result of creative thinking skills was 0.86, and the N-gain result of learning outcomes was 0.92. In conclusion, the STEM-based ecological module in differentiated classes is valid, practical, and effective in improving creative thinking skills and learning outcomes.